2008
DOI: 10.1016/j.brainres.2008.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Role of μ-calpain in proteolytic cleavage of brain l-glutamic acid decarboxylase

Abstract: Glutamic acid decarboxylase (GAD) is the rate-limiting enzyme for γ-aminobutyric acid (GABA) biosynthesis. Previously, we reported the presence of truncated forms of GAD in vivo and in vitro. In addition, an unidentified endogenous protease responsible for proteolytic cleavage of full-length GAD (fGAD) to its truncated form (tGAD) was also observed. In this communication, we report that μ-calpain is a good candidate for conversion of fGAD 67 to tGAD 67 . This conclusion is based on the following observations: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(48 reference statements)
3
17
0
Order By: Relevance
“…Together, these results suggest that calpain-mediated cleavage of GAD65 may downregulate GABA-mediated phasic inhibition. Studies similar to those described above for GAD65 also showed the calpain-mediated cleavage of GAD67 (Sha et al, 2008), which may decrease the synthesis of GABA, as observed in in vitro experiments using purified human GAD67 and recombinant µ-calpain. Silencing of the m-calpain gene had no effect on the level of truncated GAD in cultured neurons isolated from the whole brain, whereas knock-down of μ-calpain greatly decreased the cleavage of both GAD isoforms.…”
Section: Calpain-mediated Cleavage Of Glutamic Acid Decarboxylasesupporting
confidence: 65%
See 2 more Smart Citations
“…Together, these results suggest that calpain-mediated cleavage of GAD65 may downregulate GABA-mediated phasic inhibition. Studies similar to those described above for GAD65 also showed the calpain-mediated cleavage of GAD67 (Sha et al, 2008), which may decrease the synthesis of GABA, as observed in in vitro experiments using purified human GAD67 and recombinant µ-calpain. Silencing of the m-calpain gene had no effect on the level of truncated GAD in cultured neurons isolated from the whole brain, whereas knock-down of μ-calpain greatly decreased the cleavage of both GAD isoforms.…”
Section: Calpain-mediated Cleavage Of Glutamic Acid Decarboxylasesupporting
confidence: 65%
“…GAD65 and GAD67 were shown to be cleaved after transient MCAO in rats, both in the core and penumbra regions (Buddhala et al, 2012), but the mechanisms involved were not elucidated. A role for calpain in GAD cleavage was first suggested based on studies showing i) a Ca 2+ -dependent cleavage of both GAD isoforms in rat synaptosomes incubated with the Ca 2+ ionophore ionomycin, and ii) a truncation of GAD65 following depolarization of the synaptosomes with KCl (Sha et al, 2008;Wei et al, 2006). Western blot experiments with an antibody against the C-terminus of GAD65 showed the formation of a calpain-mediated cleavage product with a molecular weight of 58 kDa.…”
Section: Calpain-mediated Cleavage Of Glutamic Acid Decarboxylasementioning
confidence: 99%
See 1 more Smart Citation
“…Lys-GAD65-2 is the Ct fragment of the glutamic acid decarboxylase-65-2 (GAD65-2), which is bound to membranes of synaptic vesicles and mediates the synthesis of the inhibitory neurotransmitter c-aminobutyric acid (GABA) from the excitatory neurotransmitter glutamate. Calpain-generated Lys-GAD65-2 retains the enzymatic activity of uncleaved GAD65-2 but is no longer associated with synaptic vesicles [170][171][172] [see also Fig. 6(G)].…”
Section: Protein Fragments Their Generation Despite Deleterious Effementioning
confidence: 99%
“…The resulting supernatant was collected and centrifuged at 12,000 ϫ g for 30 min. The synaptosome-enriched pellet was gently resuspended in Krebs-Ringer phosphate buffer (123 mM NaCl, 3 mM KCl, 0.4 mM MgCl 2 , 0.5 mM NaH 2 PO 4 , 0.25 mM Na 2 HPO 4 , and 1 mg/ml glucose [pH 7.4]) (48). The synaptosome solution was aliquoted and either stimulated by the addition of 50 M NMDA and 2.2 mM CaCl 2 at 37°C for the designated time or not stimulated and then lysed in Laemmli sample buffer for Western blot analysis.…”
Section: Methodsmentioning
confidence: 99%